Adoption of six-sigma concept in New Product Development: a literature survey and analysis. (14th April 2011) - Natarajan, M.; Senthil, V.; Devadasan, S.R.; Vijay Mohan, N.; Shalij, P.R.
During recent years, many researchers and practitioners are largely concentrating on New Product Development (NPD). Owing to the absence of data on past performance history, achieving quality and reliability in NPD process has been a challenge. This paper reports a literature survey conducted in this context to identify a method for linking NPD, Total Quality Management (TQM), Reliability and six-sigma programmes. This paper reveals that a few techniques and tools are commonly used in these programmes. These common tools and techniques, which form the links to achieve quality and reliability continuously in NPD process, are to be integrated with the pillars of six-sigma concept. The paper concludes by claiming that the development of a model using these links will help in the achievement of quality and reliability continuously in NPD process.